Research to policy: Improving animal disease prevention and control in Vietnam - Chi Nguyen; Lam, Steven; Sinh Dang-Xuan; Lacasta, Anna; Unger, Fred; Nguyen Van Long; Pham Thanh Long; Bui Nghia Vuong; Dao Duy Tung; Pham Thi Ngoc; Hung Nguyen-Viet (International Livestock Research Institute, 2024)
The objectives of the workshop were to share recent research findings on African swine fever prevention and control in Vietnam and globally, identify pathways to strengthen the linkages between research and policy, and develop recommendations to enhance the effectiveness of African swine fever control measures.